Students perceptions of fake news created by artificial intelligence: The case of deep Soria - Ana Isabel Cea; Inmaculada Sánchez-Macías (OmniaScience, 2024)
Fake news and artificial intelligence are phenomena addressed in academia and research within the fields of communication and audiovisual education. As a medium and language, cinema has mirrored these challenges, exemplified by the short film Deep Soria. The primary objective proposed in this study is to ascertain whether this short film, directed by Pedro Estepa in 2021, is perceived as a mockumentary and to explore students' perceptions of the social issues it raises and the way it expresses them. An ad hoc questionnaire was employed specifically for the short film, enabling the assessment of 118 students from the Journalism and Primary Education Degree programmes at the University of Valladolid. The method used is exploratory and descriptive. Results were obtained by combining descriptive statistical analysis and content analysis of the open-ended questions in the questionnaire. Notably, the study highlights the detection of the documentary's central themes- fake news and depopulation- the use of humour, the focus on depopulation, and suggestions for incorporating more elements of "everyday reality", such as images and testimonies from the inhabitants of Soria and the city/province. At the same time, the short film has been reevaluated for its propensity to address social issues.